Case Report: Hypomorphic Ligase 4 deficiency – a paradigm of immunodysregulation - Andrade, Catarina; Cordeiro, Ana Isabel; Pinto, Marta Valente; Neves, Conceição; Martins, Catarina; Villartay, Jean-Pierre; Neves, João Farela (Frontiers in Immunology, 2025)
DNA Ligase 4 is critical to nonhomologous end joining, necessary for V(D)J recombination in T and B cell development. Ligase 4 deficiency is a rare autosomal recessive disorder caused by hypomorphic mutations in the DNA Ligase 4 gene, that can lead to a wide range of phenotypes. We describe a case of Ligase 4 deficiency causing a type of T-B-NK+ atypical SCID, highlighting the clinical and immunologic manifestations. An eight-year-old female, from São Nicolau Island (Cape Verde), presented at our hospital with a history of recurrent pneumonia and suppurative otitis, multiple skin lesions attributed to fungal and bacterial infections since the age of two, and recurrent diarrhea and growth impairment, beginning at the age of four. The laboratory workup showed almost absent B cells, marked hypogammaglobulinemia, and an impaired response to protein antigens. Flow cytometry revealed normal NK and T cell counts, but with nearly absent naïve T cells and TCR-Va7 expressing T lymphocytes, and reduced proliferative responses to mitogens and antigens. An oligoclonal Vβ repertoire was identified by FACS, and PROMIDISa analysis revealed a skewed TCRa repertoire signature. A 477 PID-related genes NGS panel identified a homozygous R278H mutation in the DNA Ligase 4 gene, previously reported to cause Ligase 4 deficiency. Immunoglobulin replacement and prophylactic therapies were started while waiting for hematopoietic stem cell transplantation. She has experienced fluctuating transaminase levels. The cutaneous biopsy was suggestive of lupus pernio. She has shown recurrent inflammatory signs in her limbs, with documented tenosynovitis on ultrasound. Homozygous R278H in Ligase 4 has been linked to various ranges of manifestations in Ligase 4 deficient patients. In our report, this genotype resulted in T-B-NK+ atypical SCID, that after proper prophylaxis has a predominant autoimmune phenotype.